The Legal Review of Petroleum Spill Case (Pertamina Oil Spill in Kalimantan) - Latif, Birkah; Kurniawan, Ade; Manggala Ayubi, Iyas (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 7 No 2 (2018), 2018)
At the end of March 2018, there was an accident in the sea of Kalimantan-Balikpapan where a Panamanian-flagged vessel caused a leak over the oil pipeline. The pipeline connects the Crude Lawe-lawe Terminal to Pertamina's Balikpapan Plant. As a result, spilled oil is estimated at 40,000 barrels and resulted in five deaths.  The aim of this study is to examine the regulation on environmental protection, especially on the oil and gas natural resources and what form the accountability of the oil spill on the shore. This paper is structured using a normative juridical approach to seek solutions to legal issues arising from such environmental cases. The study shows that the use of natural resources, which produce metals, coal, and minerals as a source of energy, oil and geothermal, should be based on the principles of environmental management, namely: equity, balances, democracy (democracy), and sustainability (sustainable) between generations. In terms of accountability both in civil liability, criminal, and an environment in accordance with the principle of direct liability (strict liability) with the occurrence of environmental pollution caused by the oil spill so legally PT Pertamina Regional East Kalimantan may be subject to the principle.